EKSISTENSI TOKOH UTAMA HIROKO MATSUKATA DALAM KOMIK HATARAKI MAN KARYA MOYOCO ANNO - Desy Wulandhary, Dewa Ayu (Humanis; Volume 9. No. 3. Desember 2014)
In the 21st century, though women still face some degrees of discrimination in the Japanese job market, there have been a number of companies that both foster women's equality and reward them on a talent based system. An existence of women should not be under estimated, Women have a mysterious power, despite not being used to their full capacity, due to their desire of marriage over lifetime employment. On literature work, a few of the Japanese carrier woman displayed in it. One of them is Moyoco Anno’s work, manga Hataraki Man. Hiroko Matsukata is a woman who works for a magazine company. She puts all she has into her work, and is known as a strong, straightforward working girl, who can at will turn herself into Hataraki man (working man) mode. Despite Hiroko's success at work, her life lacks romance.
Keywords: existence, carrier women, workaholic.